Faktor Determinan Keputusan Nasabah Menggunakan Produk Tabungan Emas - Choirunisak Choirunisak; M. Trihudiyatmanto (Jamasy: Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2021)
This study aims to examine the antecedents that influence customer decisions in saving gold at PT Pegadaian Sukorejo. Identifying the relationship between variables and indicators and knowing which constructs most influence customer decisions from several factors, namely location, service quality, brand image, knowledge, and interests.The sample in this study was the people of Sukorejo sub-district who were taken as many as 130 respondents. The research material was the result of a survey of the Sukorejo community using a questionnaire which was measured using a Likert scale and using simple random sampling technique. The statistical method uses SEM (Structural Equation Modeling) analysis.In this research, it produces interest and service quality that affects customer decisions. Location, knowledge and brand image do not affect customer decisions. Interest in mediating brand image on customer decisions. Knowledge has no effect on customer interest and interest in mediating knowledge on customer interest.